Environmental impact evaluation of a proposed steel and cement complex in the waste management scenario. Issue 2 (7th November 2022) - Panda, Chittaranjan; Pujary, Anubha; Pradhan, Nibedita; Jena, Trilochan; Mallick, Subrat Kumar
Abstract: Environmental Impact Assessment (EIA) is an important tool that identifies impact parameters, qualitatively and quantitatively predicts and evaluates the anticipated adverse and beneficial impacts. It then suggests mitigation measures and if possible alternative action. Therefore, EIA becomes mandatory for almost every planning and development processes. This paper makes analysis of the large‐scale polluting industrial processes of steel, power, and cement. It uses EIA study and consequent Environmental Management Plan (EMP) that includes elaborate mitigation measures and peripheral development. Ideally, the complete waste utilization with optimum use of resources and energy can be implemented by the industry and the same is very often mandated by regulatory authorities. The quantitative evaluation of impact by using modified Leopold matrix is separately carried out to compute total impact score (TIS) in each case. Obviously the TIS value in case of EMP with incorporation of social issues and waste utilization comes out to be a net positive value of 2218.3 offsetting the case without these issues, with a resultant high negative value of 5983.5. Sustainability aspect of the project is considered with economic, environmental and social aspects along with waste management aspects, in order to justify the viability of the project.